2018
DOI: 10.1021/acs.molpharmaceut.7b00841
|View full text |Cite
|
Sign up to set email alerts
|

The Pivotal Role of Copper in Neurodegeneration: A New Strategy for the Therapy of Neurodegenerative Disorders

Abstract: Copper is an essential trace element for the human body since it is a cofactor of several enzymes and proteins and plays a pivotal role in several biological functions (e.g., respiration, protection from oxidative damage, iron metabolism, etc.), also including the central nervous system development and functioning (e.g., synthesis of neurotransmitters, myelination, activation of neuropeptides, etc.). Therefore, copper dysmetabolism is associated with different toxic effects, mainly represented by oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 75 publications
0
54
0
Order By: Relevance
“…Many mechanisms have been considered and reviewed for the damage induced by Cu [44], Fe [49,[64][65][66], Mn [67] and Zn [49] under PD conditions; in several cases, oxidative damage, metal dyshomeostasis and α-syn aggregation have been demonstrated to be strictly related to each other.…”
Section: Metal Ionmentioning
confidence: 99%
“…Many mechanisms have been considered and reviewed for the damage induced by Cu [44], Fe [49,[64][65][66], Mn [67] and Zn [49] under PD conditions; in several cases, oxidative damage, metal dyshomeostasis and α-syn aggregation have been demonstrated to be strictly related to each other.…”
Section: Metal Ionmentioning
confidence: 99%
“…However, excessive copper may cause adverse systemic effects. It has been demonstrated that the level of copper in brain have a subtle relationship with the progress of some neurodegenerative diseases [39][40][41]. It is suggested that lead could indirectly alter copper metabolism that manifest as lead neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…44 To date, the molecular mechanisms at the basis of the pathogenic effects of ATP7A inactivation are yet to be clarified, even if it is known that this condition leads to altered Cu concentrations in cytosol, nuclei and mitochondria. 45 Although most mutations in the ATP7A gene cause Menkes' disease, some missense mutations induce a weaker disease called Occipital Horn Syndrome. 46,47 Patients with Occipital Horn Syndrome suffer from connective tissue abnormalities as with Menkes' disease patients, but do not usually present neurological symptoms and have a considerably longer average lifespan.…”
Section: Cu and Neurodegenerative Diseasesmentioning
confidence: 99%
“…At the same time, the incorporation of Cu into ceruloplasmin is impaired, thus elevated levels of free Cu are released into the bloodstream exerting extrahepatic Cu toxicity. 45 Interestingly enough, polymorphism in the ATP7B gene has also been associated with an increased risk of Alzheimer's disease (AD) and may be useful to stratify specific metabolic subtypes of AD. 48 AD is a late-onset multifactorial disease and is related to multiple risk factors.…”
Section: Cu and Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation